2022
DOI: 10.3390/vaccines10081357
|View full text |Cite
|
Sign up to set email alerts
|

Young Age, Female Sex, and No Comorbidities Are Risk Factors for Adverse Reactions after the Third Dose of BNT162b2 COVID-19 Vaccine against SARS-CoV-2: A Prospective Cohort Study in Japan

Abstract: Background: This study compared the adverse events (AEs) of the second and third doses of BNT162b2, as well as investigated the impact of vaccine recipients’ background and vaccination interval on the AEs of the third dose. Methods: We conducted a questionnaire survey of AEs among health care workers at Osaka University Dental Hospital. Chi-square tests were performed to compare AEs to the administration of second and third vaccine doses. Logistic regression analyses were conducted to identify factors influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
3
0
0
Order By: Relevance
“…In the present study, injection-site pain and fatigue were the most common adverse events after the administration of a third BNT162b2 vaccine dose. In concordance with our results are other large cohort studies from Europe and Asia in which local pain and fatigue were also found to be the most common adverse events after the third dose [ 13 , 14 , 15 ]. A recent English study investigated the severity of adverse events after the administration of the BNT162b2 third dose in healthy HCWs and HCWs with a previous COVID-19 infection and had a similar cohort size with our study, revealing that the common adverse events were the same in both groups.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, injection-site pain and fatigue were the most common adverse events after the administration of a third BNT162b2 vaccine dose. In concordance with our results are other large cohort studies from Europe and Asia in which local pain and fatigue were also found to be the most common adverse events after the third dose [ 13 , 14 , 15 ]. A recent English study investigated the severity of adverse events after the administration of the BNT162b2 third dose in healthy HCWs and HCWs with a previous COVID-19 infection and had a similar cohort size with our study, revealing that the common adverse events were the same in both groups.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the logistic regression analysis of this study support this idea, with younger individuals or females being significantly more prone to adverse reactions than males. When considered together with the results of previous studies, it is believed that this is consistently the tendency for the COVID-19 vaccine [17,18].…”
Section: Discussionsupporting
confidence: 72%
“…Studies have shown that adverse reactions to vaccines against SARS-CoV-2 are more likely to occur in young people and females and vary according to the type of vaccine [16]. Our previous studies found similar results, with younger people or females being more likely to develop adverse reactions to the first, second, and third doses of Pfizer vaccines, respectively [17,18]. However, the studies only dealt with cases caused by the monovalent Pfizer vaccine COMIRNATY ® and did not consider the effect of vaccine type.…”
Section: Introductionsupporting
confidence: 60%